Cognitive performance and mood in patients on the waiting list for liver transplantation and their relation to the model for end-stage liver disease Desempenho cognitivo e humor em pacientes em lista de espera de transplante de fígado e suas relações com modelo para doença hepática e fase terminal - Eliane C. Miotto; Karina R. Campanholo; Melissa A.R. Machado; Glaucia G.R. Benute; Mara C.S. Lucia; Renério Fráguas Jr; Telesforo Bacchella; Marcel C.C. Machado (Arquivos de Neuro-Psiquiatria)
OBJECTIVE: To investigate the links between depression and cognitive functioning in patients with Hepatitis C and other chronic liver diseases with and without the use of alcohol on the waiting list for liver transplantation and their associations with the MELD classification. METHOD: 40 patients were evaluated on a waiting list for liver transplant by a battery of neuropsychological tests, depression scales and interview at the Liver Transplant Service, of the Hospital das Clínicas University of São Paulo Medical School. RESULTS: After splitting the sample according to the education, the results showed statistical significance in the comparisons between groups of MELD > 15 and <15 in the following functions: estimated IQ, visual-spatial delayed recall and recognition as part of episodic memory and short term memory. CONCLUSION: These findings, usually found in hepatic encephalopathy, corroborated with the literature and emphasized the need to investigate in more detail the cognitive functions of these patients in order to facilitate the adoption of different conducts. OBJETIVO: Investigar as relações entre depressão e funcionamento cognitivo em pacientes portadores de hepatite C e demais doenças hepáticas crônicas com e sem uso de álcool em fila de espera para transplante hepático e suas relações com a classificação MELD. MÉTODO: Foram avaliados 40 pacientes em lista de espera para transplante hepático por bateria de testes neuropsicológicos, escalas de depressão e entrevista no Serviço de Transplante do Fígado do HC-FMUSP. RESULTADOS: Após divisão da amostra por escolaridade os resultados mostraram significância estatística nas comparações entre grupos de MELD > 15 e <15 nas funções: QI estimado, memória episódica de evocação tardia e de reconhecimento visuo-espacial e memória de curto prazo. CONCLUSÃO: As dificuldades encontradas, comuns ao quadro de encefalopatia hepática, corroboram a literatura pesquisada e enfatizam a necessidade de se investigar de maneira mais detalhada o funcionamento cognitivo destes pacientes, uma vez que diferentes condutas podem ser adotadas.